Study of bone turnover markers, procollagen type 1 N-terminal propeptide and osteocalcin in healthy and type 2 diabetes mellitus postmenopausal women - Kaushik, G. G.; Chahar, Rajesh; Chandra, Subhash (International Journal of Research in Medical Sciences, 2020)
Background: Individuals with diabetes mellitus are at increased risk of metabolic bone disease due to decrease in bone strength and quality. Several bone turnover markers like serum procollagen type I N propeptide (P1NP) and serum osteocalcin are powerful tools for studying osteoporosis and fracture risk across population to provide diagnostic and prognostic information of bone health. The aim of this study was to recognize possible correlation of levels of serum P1NP and osteocalcin in type-2 diabetic (T2DM) postmenopausal women as compared to healthy postmenopausal women. Methods: The study included 100 proven cases of type-2 diabetic postmenopausal women with age matched healthy postmenopausal women as controls. P1NP, osteocalcin, and other relevant parameters were measured. Differences between diabetics and controls were analyzed. Results: The body mass index was higher in diabetic group as compared to controls. The HbA1c% was (6.94±1.43) in diabetic group and (5.57±1.21) in non-diabetics. Low serum level of 25 (OH) D was observed both in diabetic and non-diabetic groups but significantly lower in T2DM. Procollagen type 1 N propeptide was lower in diabetic group (37.59±17.20 ng/mL) as compared to non-diabetic (52.14±24.82 ng/mL). Osteocalcin was lower (15.64±8.06 ng/ml) as compared to non-diabetic group (21.85±9.12 ng/ml). Lower osteocalcin and P1NP levels found in this study suggests slower bone metabolism with reduced bone formation in postmenopausal diabetics. Conclusions: Serum procollagen type 1 N propeptide and osteocalcin in postmenopausal diabetic women were lower as compared to non-diabetic group.